Relationship between serum lithium concentration and kidney damage in a preclinical model - Ossani, Georgina Paula (2020)
Objectives: The aim of the present study was to assess whether there is a relationship between serum lithium concentrations and the magnitude of kidney damage in a preclinical model. Methods: Thirty Wistar male rats were randomized into three groups: control group fed ad libitum powered standard diet for 3 months; and experimental groups fed ad libitum the same diet supplemented with 30 or 60 mmol/kg diet for 3 months (LowLi and HighLi groups respectively). Laboratory parameters were assessed at months 1 and 3 and histopathological changes were evaluated after 3 months. Results: Serum lithium levels in experimental rats were within therapeutic range used in humans throughout the entire experiment. After 3 months of treatment, lithium levels were statistically higher in HighLi group. Rats of the LowLi group showed dilation of cortical tubules although with similar clearance of creatinine. Rats from the HighLi group had greater histopathological damage in addition to lower creatinine clearance than the other two groups. Conclusions: Our study suggests that during long-term treatments, even with serum lithium levels within the therapeutic range used in humans, the risk of kidney damage could increase proportionally to the serum lithium concentration.